Identification of GH|MspI and GHR|AluI Gene Polymorphism and its Association with Calf Birth Weight of Grati-PO Cattle - Hartati Hartati; BDP Soewandi; AAR Hapsari; S Anwar; D Pamungkas (Indonesian Center for Animal Research and Development (ICARD), 2019)
Calf birth weight (CBW) is one of the important selection criteria to predict mature body weight and for calving ease in beef cattle. The GH and GHR genes are considered as candidate genes responsible for growth traits in cattle. The objectives of this study were to identify the polymorphism of GH|MspI and GHR|AluI genes and its association with CBW in Grati-PO cattle. A total of 186 Grati-PO cattle raised by BCRS from May to December 2017. Genomic DNA were isolated from whole blood and used in genotyping analysis using the PCR-RFLP method. The result showed that the average of CBW of Grati-PO cattle in present study was 25.58±3.31 kg. There was no statistical difference for CBW between male and female. The genotype frequency of CC, CT, and TT of GH gene were 1.1, 18.8 and 80.1 %, respectively and allele frequency of C and T of the GH gene were 0.105 and 0.895, respectively. While the genotype frequency of AA, AG, and GG of GHR gene were 66.1, 25.3 and 8.6 %, respectively, and allele frequency of A and G of GHR gene were 0.788 and 0.212, respectively. It concluded that both GH|MspI and GHR|AluI gene are polymorphic but not significantly associated with CBW in Grati-PO cattle.